Integration of AHP method in best employee selection: a multi-criteria decision analysis approach for decision making - Agung Nugroho; Bambang Winardi; Ajub Ajulian ZM (Trigin Publisher, 2023)
In an era of increasingly complex business competition, selecting the best employees has become crucial to ensure organizational productivity and success. In this endeavor, the integration of Multi-Criteria Decision Analysis Method with emphasis on Analytical Hierarchy Process (AHP) has emerged as an objective and scientific approach. This research discusses how the AHP method can be applied in the context of best employee selection by analyzing relevant criteria and pairwise comparisons that are calculated to generate relative weights. Through this process, best employee selection decisions can be made on a stronger and more transparent basis. However, the success of this method depends on the quality of the data and the assumptions used in the calculations. Although complex, AHP can provide valuable insights for decision makers in finding a balance between diverse criteria in the process of selecting the best employee.